Simultaneous label-free live imaging of cell nucleus and luminescent nanodiamonds - Gulka, Michal; Salehi, Hamideh; Varga, Bela; Middendorp, Elodie; Pall, Orsolya; Raabova, Helena; Cloitre, Thierry; Cuisinier, Frederic J G; Cigler, Petr; Nesladek, Milos; Gergely, Csilla (Scientific reports, 2020)
In recent years, fluorescent nanodiamond (fND) particles containing nitrogen-vacancy (NV) centers gained recognition as an attractive probe for nanoscale cellular imaging and quantum sensing. For these applications, precise localization of fNDs inside of a living cell is essential. Here we propose such a method by simultaneous detection of the signal from the NV centers and the spectroscopic Raman signal from the cells to visualize the nucleus of living cells. However, we show that the commonly used Raman cell signal from the fingerprint region is not suitable for organelle imaging in this case. Therefore, we develop a method for nucleus visualization exploiting the region-specific shape of C-H stretching mode and further use k-means cluster analysis to chemically distinguish the vicinity of fNDs. Our technique enables, within a single scan, to detect fNDs, distinguish by chemical localization whether they have been internalized into cell and simultaneously visualize cell nucleus without any labeling or cell-fixation. We show for the first time spectral colocalization of unmodified high-pressure high-temperature fND probes with the cell nucleus. Our methodology can be, in principle, extended to any red- and near-infrared-luminescent cell-probes and is fully compatible with quantum sensing measurements in living cells.
Keywords: Fluorescent Dyes; zubní dřeň; nanodiamanty; Cell Nucleus; Cell Line, Tumor; Spectrum Analysis, Raman; Dental Pulp; Ramanova spektroskopie; Cytological Techniques; cytologické techniky; buněčné jádro; Molecular Imaging; kultivované buňky; lidé; Nanodiamonds; Humans; fluorescenční barviva; Cells, Cultured; molekulární zobrazování; nádorové buněčné linie